Antigenic Study of Unfertilized Mouse Eggs: Cross Reactivity with SV40-Induced Antigens - Baranska, Wanda (1970)
Serum obtained from guinea pigs immunized with unfertilized C57BL/6 mouse eggs was found to be cytotoxic in the presence of complement for eggs obtained from syngeneic and allogeneic mice. The anti-egg serum was not cytotoxic for rat eggs, lymph node cells, methylcholanthrene-induced tumor cells, or 3T3 cells obtained either from syngeneic or allogeneic mice. The anti-egg serum was, however, cytotoxic for SV40-transformed 3T3 cells and C57BL/6 cells. After absorption with SV40-transformed cells, anti-egg serum lost its cytotoxicity for mouse eggs.